Thermal and hydraulic performance investigation of microchannel heat sink with sidewall square pin-fins - Fadi Alnaimat; Ahmad Rahhal; Bobby Mathew (Results in Engineering, 2024)
This paper investigates the thermal performance of straight microchannel heat sinks featuring square-shaped fins on the sidewalls using a CFD developed model. The study evaluates the performance of the heat sink in terms of the total thermal resistance (Rth) and pumping power (PPf). The results show that incorporating square-shaped fins improves thermal performance, however at the penalty of increased pressure drop. To combine heat transfer enhancement with increased pressure drop, the study uses the Figure of Merit (FOM) approach. The study finds that increasing the size of the fins reduces thermal resistance by an average of 53.5%, but Design 1, which has smaller fins, offers a higher FOM. Similarly, reducing the spacing between fins lowers thermal resistance by an average of 61.95%, but Design 5 with smaller spacing than Design 4 offers a higher FOM. Furthermore, smaller channel sizes reduce thermal resistance by an average of 51.43%, but Design 6, which has larger channel sizes than Design 7, provides a higher FOM. Additionally, reducing channel spacing reduces thermal resistance by an average of 62.2% without affecting the pumping power, and Design 8 with smaller spacing than Design 9 offers a higher FOM.